The Relationship Between Pregnant Women's Knowledge of Stunting and Their Active Participation in Antenatal Care at the Saritani Community Health Center - Yeni Eka Musdalifah; Tut Rayani Aksohini Wijayanti (The Journal General Health and Pharmaceutical Sciences Research, 2025)
Stunting is a chronic nutritional problem that has long-term impacts on the quality of human resources and is closely related to maternal health during pregnancy. Antenatal care (ANC) serves as an important promotive and preventive strategy to reduce the risk of stunting; however, pregnant women’s active participation in utilizing ANC services remains a challenge, particularly at the primary health care level. This study aims to analyze the relationship between pregnant women’s knowledge about stunting and their active participation in ANC at the Saritani Community Health Center. This research employed a quantitative analytical design with a cross-sectional approach. The population consisted of all pregnant women who attended ANC services, with a sample of 60 respondents selected through purposive sampling. Data were collected using a structured questionnaire measuring knowledge of stunting and ANC attendance behavior. Data analysis was conducted using univariate and bivariate methods, with the Chi-square test applied to examine the relationship between variables. The results showed a significant association between knowledge of stunting and ANC participation (p < 0.05). Pregnant women with higher knowledge levels were more likely to attend ANC regularly. In conclusion, improving knowledge about stunting among pregnant women is a key strategy to enhance ANC utilization and support early prevention efforts.